Marina Carr Pastures of the Unknown - Sihra, Melissa (Springer International Publishing, 2018)
This book locates the theatre of Marina Carr within a female genealogy that revises the patriarchal origins of modern Irish drama. The creative vision of Lady Augusta Gregory underpins the analysis of Carr's dramatic vision throughout the volume in order to re-situate the woman artist as central to Irish theatre. For Carr, 'writing is more about the things you cannot understand than the things you can', and her evocation of 'pastures of the unknown' forms the thematic through-line of this work. Lady Gregory's plays offer an intuitive lineage with Carr which can be identified in their use of language, myth, landscape, women, the transformative power of storytelling and infinite energies of nature and the Otherworld. This book reconnects the severed bridge between Carr and Gregory in order to acknowledge a foundational status for all women in Irish theatre.